2022
DOI: 10.3389/fonc.2022.839508
|View full text |Cite
|
Sign up to set email alerts
|

Blocking ATM Attenuates SKOV3 Cell Proliferation and Migration by Disturbing OGT/OGA Expression via hsa-miR-542-5p

Abstract: Blocking ataxia telangiectasia mutated (ATM), a crucial player in DNA repair responses, has been proposed as a promising strategy in anti-cancer therapy. Most previous studies have focused on DNA damage response-related pathways after administration of ATM inhibitors. However, ATM inhibition could potentially influence a wide range of changes in gene expression, which remain poorly defined. Here, we report that administration of the ATM inhibitor KU60019 led to impaired migration and enhanced apoptosis in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Ataxia telangiectasia mutated (ATM) could be activated in response to DNA damage, which lead to phosphorylation of downstream proteins to regulate apoptosis and cell cycle in cancer (12). It was reported that loss of ATM prolonged the diestrus phase in mice, ATM inhibition suppressed phosphoramide mustard induced destroys primordial follicles (13).…”
Section: Discussionmentioning
confidence: 99%
“…Ataxia telangiectasia mutated (ATM) could be activated in response to DNA damage, which lead to phosphorylation of downstream proteins to regulate apoptosis and cell cycle in cancer (12). It was reported that loss of ATM prolonged the diestrus phase in mice, ATM inhibition suppressed phosphoramide mustard induced destroys primordial follicles (13).…”
Section: Discussionmentioning
confidence: 99%
“…We attribute the differences in the results between U2OS and SKOV3 cells to the higher resistance of SKOV3 to PARP inhibitors and to the higher ATM activity previously reported in ovarian cancer cells [ 27 , 36 ]. A recent study showed that inhibiting ATM activity by KU-60019 in SKOV3 resulted in cell apoptosis [ 40 ]. However, it was shown that KU-60019 is 10-fold more effective than KU-55933 (the ATM inhibitor used in our study) at blocking radiation-induced phosphorylation of ATM and its targets [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple preclinical studies have analyzed the efficacy of ATM inhibitors in monotherapy or in combination with other chemotherapeutic drugs in several tumors, including OCs (Table 4). In general, these inhibitors decreased OC cell proliferation and synergized with other compounds, such as fenofibrate, an inhibitor of PPARA, 673A, or DNA-damaging agents, including ionizing radiation, trabectedin, and lurbinectedin [123][124][125][126]275].…”
Section: Atm Inhibitorsmentioning
confidence: 99%
“…Inhibition of cell migration and induction of apoptosis [123]. Synergistic cytotoxic effect in combination with fenofibrate (PPARA inhibitor) [123].…”
Section: Ku-60019 Atmmentioning
confidence: 99%
See 1 more Smart Citation